ANALISIS KUANTITATIF SISTEM PEMBIAYAAN UNTUK KREDIT INVESTASI (ALAT BERAT) PADA BANK UMUM DAN LEASING - Riri Hanifa (Jurnal Ilmiah Ekonomi Global Masa Kini)
A Company which is enganged in the procurement of heavy equipment, it would faced with the problem in adding the heavy equipment. This research was conducted in order to determine which one is the more profitable financial institutions for the company when the loan interest rate is having fluctuation which is can not be predicted before. This research is a descriptive by using  secondary data of credit calculation examples, leasing period ,prices of equipment, economic life, residual value, tax rate and interest rate  of loan. The analysis technique use two techniques: first, quantitatives analysis which is consisted of calculating a bank loan, the calculation of leasing credit, cash flow prjections,net present value and the net advantage of leasing. The result of analysis technique indicated that the alternative financing commercial bank is more profitable for company with the net present value is lower than net leasing present value and the stable if the interest.Keyword: calculating a bank loan,the calculation of leasing credit, cash flow projection, net present value and the net advantage of leasing.